Iškūz(a) - Zadok, Ran (ARAMAZD: Armenian Journal of Near Eastern Studies, 2018)
The aim of this article is to prove that Neo-Assyrian Iškūz(a), biblical Ashkenaz, is not identical with Greek Σκύθαι, i.e. the Indo-Iranian Scythians. My refutation is based mainly on the occurrence of this name as early as the first half of the second millennium BC, even before the appearance of Indo-Aryans in the Near East, and long before the Indo-Iranians who are not recorded in Near Eastern texts prior to the 1st millennium BC. First I shall discuss the textual evidence for the land of Iškūz(a) and its inhabitants (Akkadian gentilic Iškūzāyu). Next, I will analyse the scholarly attempts to reconcile the Assyrian form with the Greek form. Thereafter, the evidence for the high antiquity of the name Iškūz(a) will be presented.